The Dutch East India Company (VOC) Tasman Map and Australia: Competing Interests, Myth Making, and an Australian Icon - Stevens, Leonie; Russell, Lynette (Material Culture Review / Revue de la culture matérielle)

(untitled) (Cape Breton University Press, 2022)
The floor of the entrance to the Mitchell Library vestibule, which is part of the State Library of New South Wales, displays a stunning mosaic 1939-1941 reproduction of a seventeenth century map recording Abel Tasman’s two journeys of 1642 and 1644. It charts the west, north and southern coasts of the Australian continent, but is incomplete, thus representing the historical moment between an imagined Terra Australis Incognita, and the final survey of the east coast which presaged British colonisation. The original Tasman map, also held by the Mitchell library and currently undergoing restoration, has a strange and chequered biography. This paper explores the myths associated with what is known colloquially as the Bonaparte Tasman map, in honour of its last owner Prince Roland Bonaparte, a nephew of Napoleon. We examine its contested origins and role as an agent of Dutch East India Company imperial ambitions, relegation to forgotten cast-off when that empire collapsed, Bonaparte’s desire to gift it to the nascent Australian Commonwealth as a symbol of new nationhood, and the international subterfuge involved in its acquisition by not by the nation, but the State Library of NSW. Analysis of what was known of the map in the decades prior to its arrival in Australia challenges the conventional narratives, and we propose the biography of the Tasman map (and its embodiment in the Mitchell Library vestibule mosaic) is a study in imperialism, colonialism, federation, and power.